– THE ROLE OF BUSINESS PROCESS RE-ENGINEERING (BPR) OF SIMPLIFYING ADMINISTRATIVE PROCEDURES – A FIELD STUDY ON FEMALE ADMINISTRATIVE EMPLOYEES OF KING ABDULAZIZ UNIVERSITY IN JEDDAH - Al Zahrani, Ibtisam Ahmed; Ghaith, Nervana Abdul Rahman (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to identify the role of Reengineering with its requirements (leadership, administrative policies, strategic planning, employee empowerment, information technology, organizational structure, financial capabilities and organizational culture) in the simplification of administrative procedures from the perspective of female administrative staff at King Abdul Aziz University in Jeddah. The study is based on a descriptive analytical approach. It consists of two main parts: a theoretical section that reviews the main findings of different sources, and a field section based on a questionnaire containing (50) paragraphs. The study population consists of (1469) administrative staff at the university, the sample of the study consists of (265) administrative staff, and the data were processed statistically using the statistical package of social sciences (SPSS). The study showed several results, the most important of which were: A strong positive impact on the role of Reengineering in simplifying the administrative procedures at the University, and showed that the requirements of Reengineering represented by Information Technology, organizational structure and strategic planning are the highest availability in the work environment at the university, followed by administrative policies, leadership, organizational culture, employee empowerment and, finally, financial capabilities. The study has made several recommendations, the most important of which are: Reengineering requirements in all its dimensions at the university, and the need to establish the foundations and methods to simplify the administrative procedures, and performing comparative studies between public and private universities on the level of readiness of the educational sector and obstacles to apply reengineering and the construction of a proposed scenario of reengineering at King Abdul Aziz University in Jeddah.